Mutual Coupling Effects on Pattern Diversity Antennas for MIMO Femtocells. (17th May 2010) - Gao, Yue; Wang, Shihua; Falade, Oluyemi; Chen, Xiadong; Parini, Clive; Cuthbert, Laurie
Abstract : Diversity antennas play an important role in wireless communications. However, mutual coupling between multiple ports of a diversity antenna has significant effects on wireless radio links and channel capacity. In this paper, dual-port pattern diversity antennas for femtocell applications are proposed to cover GSM1800, UMTS, and WLAN frequency bands. The channel capacities of the proposed antennas and two ideal dipoles with different mutual coupling levels are investigated in an indoor environment. The relation between mutual coupling and channel capacity is observed through investigations of these antennas.